Effects of ICRF waves to EAST LHCD discharges on intrinsic rotations. (1st September 2022) - Jin, Y F; Lyu, B; Bae, C; Zhang, X J; Rice, J E; Wang, F D; Fu, J; Liu, H Q; Zhang, H M; Zeng, L; Chu, Y Q; Zang, Q; et al.
Abstract: Ion cyclotron range of frequencies (ICRFs) have proven to efficiently serve as a toroidal rotation source in tokamak plasmas. Recent experiments on the experimental advanced superconducting tokamak show that the rotation profiles are remarkably modified when the internal inductance ( l i ) changed. The comparisons of the ion and electron temperature profiles among ICRF-heated plasmas suggest that the change in l i can remarkably affect the toroidal rotation velocity. The scaling of rotation velocity increments as a function of the change in l i also suggests that ICRF would serve as a reliable rotation source in plasmas with larger l i decrements.